Reducing Corruption : Lessons from Venezuela - Gonzalez de Asis, Maria (World Bank, Washington, DC, 2012)
Providing information to the public is an essential but insufficient step in making local government more transparent. A participatory process is also needed, both to ensure accountability and to reinforce healthy relationships between people and government. Empirical data linked to a participatory program for institutional reform are key for eliciting broad interest in administrative organization--enabling citizens to improve municipal management. A recent World Bank program in Campo Elias, Venezuela, used an innovative and effective approach to build participatory institutional frameworks and to apply best practices in public policymaking. As a result corruption has fallen and services are delivered more efficiently. The program, which ran from April 1998 to December 1999, involved the World Bank Institute, the municipal government, and civil society. The experience shows the powerful benefits that come when local political will, technical capacity to execute reforms, and strong partnership with civil society are mixed to enhance efficiency, equity, and transparency.